2000
DOI: 10.1007/s000590050011
|View full text |Cite
|
Sign up to set email alerts
|

Enteroviral Cardiomyopathy: Bad News for the Dystrophin-Glycoprotein Complex

Abstract: Genetic deficiency of the dystrophin-glycoprotein complex causes hereditary dilated cardiomyopathy. Enteroviruses can also cause cardiomyopathy and we have recently described a potential molecular mechanism for enterovirus-induced dilated cardiomyopathy. The coxsackieviral protease 2A proteolytically cleaves and functionally impairs dystrophin. Additionally, during infection with coxsackievirus B3, the dystrophin-glycoprotein complex becomes disrupted and the sarcolemmal integrity is lost. This review article … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(14 citation statements)
references
References 42 publications
0
13
0
1
Order By: Relevance
“…The cardiac phenotype of some dystrophin mutations was found to result from an alteration of the promoter region required for specific expression of this protein in cardiomyocytes, or from conformational changes of the dystrophin rod or hinge regions (221). It is worth mentioning that the disruption of the dystrophin complex was also found in viral myocarditis (222,223), which may provide an explanation for the acquired form of DCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…The cardiac phenotype of some dystrophin mutations was found to result from an alteration of the promoter region required for specific expression of this protein in cardiomyocytes, or from conformational changes of the dystrophin rod or hinge regions (221). It is worth mentioning that the disruption of the dystrophin complex was also found in viral myocarditis (222,223), which may provide an explanation for the acquired form of DCM.…”
Section: Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…Certainly, virus infection directly damages heart cells either by disrupting cardiac function [1,2,39], or directly killing infected myocardial cells [12,20,29]. The ultimate importance of direct virus pathogenicity likely will depend on the extent of infection.…”
Section: Introductionmentioning
confidence: 98%
“…Dendritic cells in the mice also become infected and affect levels of IL-10, IL-6, and TNF-␣ (36). Other studies with animal models have demonstrated that enteroviral protease 2A cleaves dystrophin, thereby disrupting the integrity of the sarcolemmal dystrophin-glycoprotein complex (37)(38)(39).…”
Section: Discussionmentioning
confidence: 99%